2017
DOI: 10.1038/s41598-017-15061-w
|View full text |Cite
|
Sign up to set email alerts
|

The comprehensive expression analysis of circular RNAs in gastric cancer and its association with field cancerization

Abstract: Circular RNAs comprise a new class of long noncoding RNAs characterized by their 5′ and 3′ ends covalently joined. Previous studies have demonstrated that some circular RNAs act as microRNA sponges, and are associated with cellular proliferation in cancer. We were the first to analyze the global expression of circular RNAs in samples of patients without gastric cancer, gastric cancer, and matched tumor-adjacent gastric tissue. Among the samples, we identified 736 previously annotated circular RNAs by RNA-Seq. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 53 publications
2
32
1
Order By: Relevance
“…The circRNA expression pro les in GC further con rmed that circRNAs were closely associated with GC. However, only few circRNAs were ascertained to regulate carcinogenesis in GC [34][35][36]. In the present study, hsa_circ_000780 was selected as a targeted circRNA to validate the accuracy of the microarray results.…”
Section: Discussionmentioning
confidence: 98%
“…The circRNA expression pro les in GC further con rmed that circRNAs were closely associated with GC. However, only few circRNAs were ascertained to regulate carcinogenesis in GC [34][35][36]. In the present study, hsa_circ_000780 was selected as a targeted circRNA to validate the accuracy of the microarray results.…”
Section: Discussionmentioning
confidence: 98%
“…Considering that epigenetic alterations could potentially be detected in the early stages of carcinogenesis [ 9 , 40 , 52 ], our analysis, comparing the NC and ADJ tissues, allows for better comprehension of tumor progression and highlights alterations that could be used as prognostic biomarkers. Although a few studies have demonstrated some discrepancies of piRNA expression between blood and cancer tissues, their potential as cancer biomarkers is remarkable [ 43 , 53 ]. In this study, we found eight possible piRNAs and some that are exclusive to GC and ADJ, such as piR-31355* ( Figure 2 B and Figure 3 B).…”
Section: Discussionmentioning
confidence: 99%
“…The expression profiles of circRNAs in GC further confirmed that circRNAs were closely associated with GC. However, only a small number of circRNAs were ascertained to regulate carcinogenesis in GC [25][26][27]. In this study, hsa_circ_000780 was selected as a targeted circRNA to validate the accuracy of microarray results.…”
Section: Discussionmentioning
confidence: 99%